KEPRIBADIAN IDEAL KONSELOR ISLAM BERDASAR NILAI DALAM QASIDAH YA AR HAMAR ROHIMIN KARYA HABIB ABDULLAH BIN HUSAIN BIN THOHIR BAA ALAWI نيمحرلا محرأ اي ةديصق - Mohammad Zuhal; M. Syakur (Fakultas Dakwah Universitas Ibrahimy, 2022)
There have been many counseling service practices that are below standard and even deviate, providing counseling assistance that is not optimal and even deviating from these items will certainly affect the results that will be obtained by the counselee, the counselee will cer-tainly be detrimental because of it. One of the factors that can be the cause of the emergence of these problems is a counselor who is less or not ideal. Unlike school/educational counseling which has the main reference in the form of the Minister of Education Regulation Number 27 of 2008 concerning Academic Qualification Standards and Counselor Competencies, which contains ideal writings that must be owned by education/school counselors, in Islamic counseling there is no single main guideline that must be followed. become a reference for the ideal personality of Islamic counselors. In ن——– by Habib Abdullah bin Husain bin Thohir, there is a prayer verse that discusses the criteria for ideal leaders, which then these criteria in this study will be discussed from the point of view of Islamic counseling, especially the ideal counseling of Islamic counselors. The problem that will be discussed in this research is how is the ideal personality of Islamic counselors based on values in the work of Habib Abdullah Bin Husain Bin Thohir Baa Alawi? The method that will be used to discuss these problems is a qualitative method with the type of hermeneutic research, and the data analysis uses the objectivist Hika cycle (objectivist hermeneutics) from Gadamer›s part-whole path. This study tries to understand what is contained in the verse about the criteria of an ideal leader, and then discussed from the point of view of Islamic counseling in the aspect of the ideal personality that an Islamic counselor must have. The ideal personality of an Islamic counselor based on the values contained in is unique because there has never been an ideal personality that has been raised with the same composition and discussion material, namely Amar Ma›ruf Nahi Mungkar, Faith and Fear, Obeying the Rules, Loving People. People Sholeh, Fair, and Confidentiality (Gives a Sense of Security Especially in terms of Confidentiality).